Effect of Pluronic F127 Concentration on Gelling Temperature and other Parameters of Lomustine Mucoadhesive In-Situ Gel - Maryam H. Alaayedi; Nidhal Khazaal Maraie (Iraqi Journal of Pharmaceutical Sciences, 2024)
Pluronic F127 is one of the widely used thermoreversible gelling agent, and used in sol-to-gel transformation. It has been used to localize drug delivery such as nose-to-brain delivery which allows the direct targeting of drug molecules bypassing the systemic effect and BBB (Blood Brain Barrier). The anticancer drug lomustine had poor oral bioavailability in addition to its serious side effect, therefore, developing more effective drug delivery with direct targeting towards the brain through intra-nasal administration applying nanoemulsion-based-in situ gel technology is a promising alternative. The work involved formulation of lomustine as in situ gel using Pluronic F127 and study the effect of the polymer on solution to gel transition temperature, gelation behaviour, spreadability, mucoadhesive force, residence time and residence drug percentage, as well as in vitro drug release. The results showed acceptable pH and high drug content, beside increased Pluronic percentage (from 15 to 20%) led to reduced gelation temperature from 33°C to 27°C and spreadability, improved gelling properties from + to +++, increasing mucoadhesive force from 4965.33 to 9866.30 dyne/cm2 as well as prolonged residence time from 30 to 66 min and in vitro drug release where was 120 min for 100% drug release from F1 that contained 15% of the polymer to 210 min for F3 with 20% polymer. Therefore, modifying the Pluronic F127 percent in the in situ formulas could optimize the required formula for targeting the anticancer to treat brain cancer via nose-to-brain delivery.